Evaluation of Hematotoxicity in Female Wistar Rats Following Sub-Acute Inhalation Exposure to Polyethylene Microplastic - Sulistomo, Hikmawan Wahyu; Setyowati, Anisa; Situmorang, Melani Chysti; Sulistiani, Ita; Wardani, Dewi Azar Nuria; Gusti, Kharisma Ciptaning; Nurdiana, Nurdiana; Kusuma, Ihda Dian; Rahardjo, Bambang; Reksohusodo, Subandi (JURNAL INFO KESEHATAN, 2024)
Polyethylene (PE) becomes a source of microplastics that can be widely distributed through the digestive and respiratory systems. However, its effects on blood cells are still being investigated. This study aims to analyze the impact of Polyethylene Microplastic (PE-MPs) exposure on the blood of female rats, including erythrocytes, leukocytes, and platelets. This study used female Wistar rats, which were divided into control and PE-MP groups. PE-MP was administered via whole-body inhalation at a concentration of 15 mg/m³ for 4 hours daily for 28 days. The absorption of plastic particles detected in the human bloodstream is likely to occur through mucosal contact (either through ingestion or inhalation). After the exposure period, the rats were euthanized to collect blood samples through the heart. A complete blood count was performed using an automatic hematology analyzer, and blood morphology was analyzed using thin blood smears. This study used the Mann-Whitney test. PE-MP exposure increased erythrocyte and platelet counts without a corresponding rise in leukocytes. Erythrocytes showed abnormal morphology (12.73% with ovalocytes and tear-shaped cells). Erythrocyte indices (MCV, MCH, MCHC) showed no significant differences. Platelet count rose by 1.7% (p-value= 0.017). Leukocyte and neutrophil counts were lower (0.84 and 0.94 times lower, respectively), while lymphocytes and monocytes were higher (1.03 and 1.61 times higher, respectively) in the PE-MP group compared to controls. The neutrophil-to-lymphocyte ratio did not differ significantly. PE-MP exposure in rats disrupts blood parameters, altering erythrocyte morphology and increasing platelet counts. Potential causes include oxidative stress, immune responses, and compensatory mechanisms. Study limitations include a small sample size and exclusive focus on inhalation exposure. Integrating multiple exposure routes (inhalation, ingestion, dermal) could offer a broader view of microplastic impacts. Future research with larger samples, diverse doses and durations, and exploration of additional markers or organ-specific effects is crucial for understanding PE-MP toxicity in real-world scenarios.